2007
DOI: 10.1210/me.2006-0096
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Transcript Profiling and Phylogenetic Analysis Identifies Suppressor of Cytokine Signaling 2 as a Direct Signal Transducer and Activator of Transcription 5b Target in Liver

Abstract: The GH-activated signal transducer and activator of transcription 5b (STAT5b) is an essential regulator of somatic growth. The transcriptional response to STAT5b in liver is poorly understood. We have combined microarray-based expression profiling and phylogenetic analysis of gene regulatory regions to study the interplay between STAT5b and GH in the regulation of hepatic gene expression. The acute transcriptional response to GH in vivo after a single pulse of GH was studied in the liver of hypophysectomized r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 65 publications
3
66
0
Order By: Relevance
“…This interaction was shown to be critical for the regulation of specific subsets of metabolic genes (24). (69) analyzed gene expression profiles in liver tissue from mice that carry truncated GHRs that impair STAT5A/B signaling, and Vidal et al (84) analyzed gene expression in mice on GH stimulation. On the basis of these experiments, a large set of genes was identified whose expression was altered on the deletion of STAT5A/B.…”
Section: Cytokine-stat5a/b Signaling In the Livermentioning
confidence: 99%
“…This interaction was shown to be critical for the regulation of specific subsets of metabolic genes (24). (69) analyzed gene expression profiles in liver tissue from mice that carry truncated GHRs that impair STAT5A/B signaling, and Vidal et al (84) analyzed gene expression in mice on GH stimulation. On the basis of these experiments, a large set of genes was identified whose expression was altered on the deletion of STAT5A/B.…”
Section: Cytokine-stat5a/b Signaling In the Livermentioning
confidence: 99%
“…Global gene expression analysis has identified many genes that respond to GH rapidly, several of which are known to be direct targets of STAT5 (60)(61)(62). These early GH response genes include several transcription factors that show sex-biased expression.…”
mentioning
confidence: 99%
“…Given that the fish embryos undergo dynamic cell movement in early development, e.g., gastrulation movements (Chen et al 2009), it is possible that the GH/GHR pathway may participate in the regulation of cell movement during early development. It was also reported that GH/Stat5b can directly regulate the transcription of a Wnt signaling element (frizzled4) and suppressors of cytokine signaling (Vidal et al 2007), thus it is also possible that GH/GHR pathway may crosstalk with the other pathways to regulate the early development of fish.…”
Section: Discussionmentioning
confidence: 99%